THE EUROPEAN UNION AND HEALTH SECURITY IN THE CONTEXT OF THE COVID-19 PANDEMIC - Ćurčić, Slađana (National interest, 2023)
The paper considers health security in the European Union, before and during the COVID-19 pandemic, through the analysis of the EU strategic-normative, political and institutional framework in this area. The aim was to determine whether the changes in the field of public health at the EU level, induced by the COVID-19 pandemic, contributed to defining a clear approach of the Union to health security and to strengthening its global role in this field. Although the concept of health security is still subject to different and broad interpretations, its practical importance comes to the fore primarily in periods of health crises. Thus, at the EU level, pandemics and epidemics of infectious diseases, as well as threats from bioterrorism, have stimulated more intensive reflections on health security in a theoretical, political and practical sense. Therefore, in this paper health security is analyzed with a focus on infectious diseases as one of the serious and emerging health threats. Methodologically, the paper is based on content analysis, first of all academic literature on health security, the most important strategic documents, health policies and mechanisms of the EU. The analysis showed that the health security field at the EU level has not yet been developed to such an extent that we could talk about a coherent approach to health security, that reflects a collective (European) vision. Namely, that approach varies from the humanocentric paradigm, which is embodied in the Union's commitment to human rights, human development and the general health needs of “ordinary” people, to the traditional, state-centric one, which came to the fore through the unilateral actions of the members during the COVID-19 pandemic. Finally, awareness of the need for a broader, common approach to serious health threats, became clearer after dealing with the consequences of this isolationist policies of the member states.Therefore, we still couldn’t talk about global EU actorness in this area, despite the Union's expressed desire for a leadership role, especially stimulated by the COVID-19 pandemic. Namely, the COVID-19 crisis simultaneously shed light on numerous vulnerabilities and shortcomings of the EU health security regime and opened the way for reforms and improvements in this area. Taking into account that the COVID-19 crisis caused both geopolitical consequences and a crisis in international relations, this is an additional reason for strengthening the position of the EU in global health governance. Therefore, at this moment, the changes in the EU, prompted by COVID-19 can be seen as just one more step on the way to strengthening the future position of the EU in global health security.
Keywords: European Union; health security; COVID-19 pandemic; crisis